Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.